2010
DOI: 10.4061/2010/519028
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Progenitor Cells and Their Orthopedic Applications: Forging a Path towards Clinical Trials

Abstract: Mesenchymal progenitor cells (MPCs) are nonhematopoietic multipotent cells capable of differentiating into mesenchymal and nonmesenchymal lineages. While they can be isolated from various tissues, MPCs isolated from the bone marrow are best characterized. These cells represent a subset of bone marrow stromal cells (BMSCs) which, in addition to their differentiation potential, are critical in supporting proliferation and differentiation of hematopoietic cells. They are of clinical interest because they can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 127 publications
0
63
0
1
Order By: Relevance
“…At least 15 different BMPs have been identified in humans, and disruptions in BMP signaling result in a variety of skeletal and extraskeletal anomalies differentiation [3,4,7]. Mesenchymal stem cells (MSCs) are multipotent progenitor cells with the capacity of differentiating into osteoblastic, chondrogenic, and adipogenic lineages [8][9][10][11][12][13]. MSCs have attracted significant attention for their potential role in stem cell biology and regenerative medicine [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 15 different BMPs have been identified in humans, and disruptions in BMP signaling result in a variety of skeletal and extraskeletal anomalies differentiation [3,4,7]. Mesenchymal stem cells (MSCs) are multipotent progenitor cells with the capacity of differentiating into osteoblastic, chondrogenic, and adipogenic lineages [8][9][10][11][12][13]. MSCs have attracted significant attention for their potential role in stem cell biology and regenerative medicine [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent progenitor cells with the capacity of differentiating into osteoblastic, chondrogenic, and adipogenic lineages [8][9][10][11][12][13]. MSCs have attracted significant attention for their potential role in stem cell biology and regenerative medicine [12][13][14][15][16][17][18]. Through a comprehensive analysis of the 14 types of BMPs' osteogenic activities, we demonstrated that BMP9 is among the most osteogenic BMPs that induce osteoblastic differentiation of MSCs by regulating a distinct set of downstream mediators of osteogenic signaling [19][20][21][22][23][24][25][26][27], as well as through extensive crosstalk with other major signaling pathways [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional mesenchymal stem cells (MSCs) are nonhematopoietic multipotent cells, which have the capacity to differentiate into osteoblastic, chondrogenic, and adipogenic lineages although MSCs have been shown to differentiate into other lineages [8][9][10]. Besides bone marrow, MSCs have been isolated from other tissues, including periosteum, brain, liver, bone marrow, adipose, skeletal muscle, amniotic fluid, and hair follicle lineages [9,10]. While MSCs isolated from various tissues share many similar characteristics, they exhibit discernible differences in their expression profile and differentiation potential [9].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Utilizing both strategies is critical because manipulation of mesenchymal cell differentiation has shown promise in regeneration of native tissue. [12][13][14] Currently, there is considerable interest in defining ideal ligament scaffolds and therefore our goal has been to create a novel engineered neoligament tissue. In this study, we have examined growth of mesenchymal cells on a synthetic scaffold prepared from biodegradable polymers in the presence of ligament-related growth factors to assess whether such biologically enhanced scaffolds have the potential to restore native ligamentous tissue and architecture.…”
Section: Introductionmentioning
confidence: 99%